Factors Driving the Use of Video on Demand (VoD) - Reagen Yohanes Sayoga (Journal of E-business and Management Science, 2023)
The purpose of this research is to investigate the factors that influence the current and future use of VoD applications. The factors investigated based on perceived value are ease of use, convenience value, monetary value, emotional value, social value and identity salience. In addition, predictions are made on the factors of user value in understanding the use of VoD. The research design uses a survey of users who subscribe to VoD services in Jabodetabek. The target sample is 300 VoD users. The data analysis method uses the partial least square-structural equation modeling (PLS-SEM).